A New and Faster Test to Assess Vestibular Perception - Dupuits, Bart; Pleshkov, Maksim; Lucieer, Florence; Guinand, Nils; Pérez Fornos, Angelica; Guyot, Jean Philippe; Kingma, Herman; van de Berg, Raymond (Frontiers in Neurology, 2019)
Objective: Clinical vestibular testing mainly consists of testing reflexes, but does not routinely include testing for perceptual symptoms. The objective of this study was to investigate a new and faster test for vestibular perception, and to compare its results with previous studies. Methods: Fifty-five healthy subjects with no prior vestibular complaints were included and divided into three age groups. Vestibular perceptual thresholds were measured using a hydraulic platform in the dark. The platform delivered twelve different movements: six translations (forward, backward, right, left, up and down) and six rotations/tilt (yaw left, yaw right, pitch forward, pitch backward, roll left and roll right). The subject had to report the correct type and direction of movements. Thresholds were determined by a double confirmation of the lowest threshold. General trends in thresholds like relative interrelationship and the influence of age were analyzed and compared with values reported previously. Results: Mean thresholds of age groups ranged between 0.092m/s2 and 0.221m/s2 for translations, and between 0.188 deg/s2 and 2.255deg/s2 for rotations. The absolute values differed from previous reports, but the relative interrelationship of thresholds between type and direction of motion remained. An association between age and vestibular thresholds was found, similar to previous reports. Conclusion: This new and faster test for vestibular perception showed comparable patterns in perceptual thresholds when compared to more research oriented, lengthy tests. This might pave the way for establishing vestibular perception testing protocols useful for the clinic.